Система обробки та реєстрації медико-біологічних параметрів для універсального комплексу клінічного моніторингу у сімейній медицині - Сітнікова, Оксана Олександрівна (НТУ "ХПІ", 2017)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.11.17 – біологічні та медичні прилади і системи. – Національний технічний університет "Харківський політехнічний інститут", Харків, 2017 р. Робота присвячена удосконаленню комплексу клінічного моніторингу у сімейній медицині на основі побудови системи обробки та реєстрації медико-біологічних параметрів. У роботі запропоновано математичну модель процедури надання медичної допомоги сімейним лікарем на основі Протоколу надання медичної допомоги, що дозволило підвищити точність та повноту медико-діагностичних даних при формуванні контрольно-діагностичних рішень. Запропоновано метод обробки та реєстрації медико-біологічних параметрів на основі створення системи ознак медико-діагностичної інформації. Отримав подальший розвиток метод математичного моделювання медичних систем на основі використання методу компараторної ідентифікації та апарату алгебро-логічних перетворень. Практичне значення роботи полягає у побудові інформаційно-логічних моделей систематизації медико-біологічної інформації для формалізації поповнення та екстракції бази знань, що дозволило автоматизувати обробку медичних даних та прискорити пошук та реєстрацію даних для діагностики та прийняття рішень.

Dissertation for the philosophy doctor degree in the technical sciences area for specialty 05.11.17 – Biological and Medical Devices and Systems – National Technical University "Kharkov Polytechnic Institute", Kharkov, 2017. The work is dedicated to the improvement of the clinical monitoring complex in family medicine on the basis of the construction a system for processing and recording medical and biological parameters. A mathematical model of the procedure for providing medical assistance to a family doctor on the basis of the Protocol for the provision of medical care was proposed, which made it possible to improve the accuracy and completeness of medical and diagnostic data in the development of diagnostic and control solutions. Mathematical models of quantitative analysis and maximization of the information content of medical and biological signals have been developed, which allowed to formulate requirements when planning the protocols used in making control and diagnostic decisions by the family doctor. A method for processing and recording medical and biological parameters based on the development of a system of medical diagnostic information was proposed, which reduced the amount and time of processing and recording clinical monitoring data. The method of mathematical modeling of medical systems based on the use of the comparator identification method and the models of algebra-logical transformations was further developed, which allowed improving the diagnostic and prophylactic activity of the family doctor. The practical significance of the work consists in constructing information-logical models of the systematization of medical and biological information for the formalization of recording and extraction of the knowledge base, which made it possible to automate the processing of medical data and speed up the search and registration of data for diagnosis and decision-making. This allowed to reduce risks when making decisions in the complex of clinical monitoring of the family medicine system.
Processing and recording system of medical and biology parameters for clinical monitoring universal complex in family medicine
Keywords: сімейна медицина; клінічний моніторинг; медико-діагностична інформація; медико-біологічні параметри; дисертації; family medicine; clinical monitoring; medical and diagnostic information; medical and biological parameters; 681.2.08:53.083.62:53.082.6